2011
DOI: 10.2310/10.2310/8000.2011.110253
|View full text |Cite
|
Sign up to set email alerts
|

Use of personal protective equipment in Canadian pediatric emergency departments

Abstract: Objective: Numerous barriers to maintaining infection control practices through the use of personal protective equipment (PPE) exist in the emergency department (ED). This study examined the knowledge, self-reported behaviours, and barriers to compliance with infection control practices and the use of PPE in Canadian pediatric EDs. Methods: A self-administered survey instrument consisting of 21 questions was developed and piloted for this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
3
15
0
1
Order By: Relevance
“…[47][48][49][50][51] In some cases, HCP also report uncertainty of which protective barriers to use and when, reflecting inadequate training or knowledge retention. 52,53 Several intervention studies have sought to improve HCP adherence to standard precautions in the ED (Table 2). 44,[54][55][56][57][58] Educational programs have employed in-service lectures, smallgroup discussions, and written materials highlighting the risks posed by bloodborne pathogens.…”
Section: Hand Hygienementioning
confidence: 99%
“…[47][48][49][50][51] In some cases, HCP also report uncertainty of which protective barriers to use and when, reflecting inadequate training or knowledge retention. 52,53 Several intervention studies have sought to improve HCP adherence to standard precautions in the ED (Table 2). 44,[54][55][56][57][58] Educational programs have employed in-service lectures, smallgroup discussions, and written materials highlighting the risks posed by bloodborne pathogens.…”
Section: Hand Hygienementioning
confidence: 99%
“…They are also exposed to both seasonal and emerging respiratory infectious diseases. In one paediatric ED setting, only 1-12% of clinicians reported that they always or usually wore a mask or eye protection, while assessing febrile respiratory patients during winter [28]. Although gloves are worn frequently, patient safety may be compromised by misuse, such as not changing them between dirty and clean tasks on the same patient or between different patients and/or failing to comply with hand hygiene before and after use, which often contaminates the clinician's hands [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly cited factors contributing to sub-optimal compliance with PPE in healthcare include inadequate knowledge and training, perception of risk, organisational culture and environmental barriers [32,33]. Reid et al [28] identified knowledge, access to PPE, patient diagnosis and unit culture, in the ED context, as factors influencing PPE compliance.…”
Section: Introductionmentioning
confidence: 99%
“…4 Two studies from Canada found 44% of nurses in 6 hospitals 5 and 11% of doctors in 14 hospitals reported they properly adhered to FPE. 6 Such suboptimal adherence rates are of great concern because it is estimated that 1 in 4 health care workers contract a communicable respiratory illness through work. 7 Furthermore, FPE has been cited as the most uncomfortable and problematic of all types of personal protective equipment, and is often more poorly adhered to than other components of standard precautions such as hand washing and glove use.…”
mentioning
confidence: 99%